A rare cause of duodenal stricture. (8th February 2011) - Al-Hilou, Hossam; Carroll, Nicholas; Jah, Asif; Davies, Susan; Parkes, Miles
Abstract : The authors report the case of a 62-year-old lady who had never lived overseas and who presented with symptoms of gastric outflow obstruction with weight loss. Endoscopic investigation demonstrated a tight, impassable stricture in the second part of the duodenum, with CT demonstrating a mass and surrounding lymphadenopathy. Extrinsic compression at this site in UK residents in late middle age usually heralds a diagnosis of pancreatic malignancy. In this case, investigation by endoscopic ultrasound with sampling of an otherwise inaccessible lymph node to obtain 'micro biopsies' by fine needle aspiration allowed a diagnosis of duodenal tuberculosis. The patient has responded to appropriate antibiotic therapy and is now well.